2018
DOI: 10.1302/2046-3758.71.bjr-2017-0074.r2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation into the influence of loading conditions in biomechanical testing of locking plate fracture fixation devices

Abstract: ObjectivesSecondary fracture healing is strongly influenced by the stiffness of the bone-fixator system. Biomechanical tests are extensively used to investigate stiffness and strength of fixation devices. The stiffness values reported in the literature for locked plating, however, vary by three orders of magnitude. The aim of this study was to examine the influence that the method of restraint and load application has on the stiffness produced, the strain distribution within the bone, and the stresses in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 53 publications
(114 reference statements)
2
24
1
1
Order By: Relevance
“…50,51 However, they used a highly constrained experimental setup, which is likely to have influenced the results. 31 Additionally, Röderer et al 51 measured very small values of IFM in one cadaveric model (0.05 mm at 1000 N) examining an alternative screw type, which they found dramatically increased the IFM to 0.16 mm at 1000 N. A previous experimental and computational study by Luo et al 28 used a similar loading regime to the present study and found IFM values for a TomoFix implant placed in the same orientation as the present study to be 0.93 mm at 2000 N.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 However, they used a highly constrained experimental setup, which is likely to have influenced the results. 31 Additionally, Röderer et al 51 measured very small values of IFM in one cadaveric model (0.05 mm at 1000 N) examining an alternative screw type, which they found dramatically increased the IFM to 0.16 mm at 1000 N. A previous experimental and computational study by Luo et al 28 used a similar loading regime to the present study and found IFM values for a TomoFix implant placed in the same orientation as the present study to be 0.93 mm at 2000 N.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption dramatically increases the construct stiffness while also lowering predictions of plate stress. 31 Additionally, previous HTO computational studies have not considered the influence of healing at the fracture site.…”
Section: Introductionmentioning
confidence: 99%
“…Rigid implants prevent stability by controlling the movement between implants and segments. High shear stress and stiffness after rigid fixation increase the load transfer through the implant and bone-implant interface, leading to damage of the bone and early failure of the interface [32][33][34] . The basic mechanics of the micro-dynamic pedicle screw reduce the stress concentration between the parts of the implant and the bone-implant interface, permitting physiological load transfer and appropriate spinal motion.…”
Section: Stability Of the Novel Micro-dynamic Pedicle Screwmentioning
confidence: 99%
“…Such boundary conditions rarely reflect in vivo reality, but approximate it to different degrees. The importance of boundary conditions depends on the problem and the outcome variable being investigated [13]. In most experimental mechanical testing studies and FE models the contribution of muscles and ligaments is ignored [4,6].…”
Section: Geometrymentioning
confidence: 99%